Assessment of Blood-Brain Barrier Permeability by Dynamic Contrast-Enhanced MRI in Transient Middle Cerebral Artery Occlusion Model after Localized Brain Cooling in Rats - Kim, Eun Soo; Lee, Seung-Koo; Kwon, Mi Jung; Lee, Phil Hye; Ju, Young-Su; Yoon, Dae Young; Kim, Hye Jeong; Lee, Kwan Seop (Korean journal of radiology, 2016)
The purpose of this study was to evaluate the effects of localized brain cooling on blood-brain barrier (BBB) permeability following transient middle cerebral artery occlusion (tMCAO) in rats, by using dynamic contrast-enhanced (DCE)-MRI. Thirty rats were divided into 3 groups of 10 rats each: control group, localized cold-saline (20℃) infusion group, and localized warm-saline (37℃) infusion group. The left middle cerebral artery (MCA) was occluded for 1 hour in anesthetized rats, followed by 3 hours of reperfusion. In the localized saline infusion group, 6 mL of cold or warm saline was infused through the hollow filament for 10 minutes after MCA occlusion. DCE-MRI investigations were performed after 3 hours and 24 hours of reperfusion. Pharmacokinetic parameters of the extended Tofts-Kety model were calculated for each DCE-MRI. In addition, rotarod testing was performed before tMCAO, and on days 1-9 after tMCAO. Myeloperoxidase (MPO) immunohisto-chemistry was performed to identify infiltrating neutrophils associated with the inflammatory response in the rat brain. Permeability parameters showed no statistical significance between cold and warm saline infusion groups after 3-hour reperfusion 0.09 ± 0.01 min(-1) vs. 0.07 ± 0.02 min(-1), p = 0.661 for K(trans); 0.30 ± 0.05 min(-1) vs. 0.37 ± 0.11 min(-1), p = 0.394 for kep, respectively. Behavioral testing revealed no significant difference among the three groups. However, the percentage of MPO-positive cells in the cold-saline group was significantly lower than those in the control and warm-saline groups (p < 0.05). Localized brain cooling (20℃) does not confer a benefit to inhibit the increase in BBB permeability that follows transient cerebral ischemia and reperfusion in an animal model, as compared with localized warm-saline (37℃) infusion group.